Efficient synthesis of diethyl benzo[c]cinoline-3, 8-dicarboxylate for fluorescence quenching materials. (14th March 2017) - Wang, Ning; Yang, Jin-Chuang; Chen, Li-Dong; Li, Jia; An, Yue; Lü, Cheng-Wei; Tian, Yun-Qi
Abstract : Diethyl benzo[ c ]cinoline-3, 8-dicarboxylate was synthesized via a simplified method and was applied as a highly efficient fluorescence sensor for detection of TNP for the first time. Abstract : An intriguing reaction for direct construction of diethyl benzo[ c ]cinoline-3, 8-dicarboxylate (2 ) was developed. The synthetic route was improved, the operation procedure was simplified, and the total yield was enhanced. The single crystal structure of the intermediate was obtained and a possible reaction mechanism was speculated. Moreover, compound2 and its hydrolysis product were employed as fast and extremely efficient sensors for sensitive optical detection of picric acid (TNP) for the first time. These fluorescence quenching materials are capable of sensing TNP in real water samples, which is important in terms of practical application. In addition, we also analysed the working principle for the detection of TNP by density functional theory.